2013
DOI: 10.1097/hjh.0b013e32835f5721
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of valsartan in hypertensive children 6 months to 5 years of age

Abstract: Although a dose-response trend was observed, statistical significance was not achieved during the dose ranging (primary endpoint) or the placebo-withdrawal periods of the study. However, valsartan demonstrated significant reductions in BP compared with baseline and provided consistent reductions over 26 weeks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 21 publications
1
4
0
5
Order By: Relevance
“…18 Schaefer et al also demonstrated a good tolerability of the drug even in children with hypertension. 19 Our study substantiate similar standpoint to the safety and efficacy of Valsartan at higher doses reveled in other population. Current study upholds the use of the drug at higher dose effective and safe antihypertensive treatment modality.…”
Section: Discussionsupporting
confidence: 74%
“…18 Schaefer et al also demonstrated a good tolerability of the drug even in children with hypertension. 19 Our study substantiate similar standpoint to the safety and efficacy of Valsartan at higher doses reveled in other population. Current study upholds the use of the drug at higher dose effective and safe antihypertensive treatment modality.…”
Section: Discussionsupporting
confidence: 74%
“…Препараты этого класса ингибируют вазоконстрикцию, уменьшают гипертрофию левого желудочка, снижают протеинурию и при этом хорошо переносятся пациентами. Показана эффективность лозартана [3,26,32], валсартана [22,24,33,34], кандесартана [35], олмесартана [36], телмисартана [20] для снижения артериального давления (на 6-13 мм рт.ст.) у детей с артериальной гипертензией.…”
Section: медикаментозная терапия артериальной гипертензииunclassified
“…They should be avoided in patients with acute kidney injury. Adverse effects reported in trials for patients less than 6 years of age have led to some safety concerns [42,43], though they are used with some regularity in this age group. ARBs do not inhibit the breakdown of kinins and therefore cause cough less frequently than ACE inhibitors.…”
Section: Indications and Contraindicationsmentioning
confidence: 99%